Pengenalan Alat Press pada UMKM untuk Optimalisasi Pengemasan Produk di Desa Sukamukti - Elvira Novita Tanjung; Ninik Paryati; Setyo Supratno (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This activity aims to optimize the packaging of Sukamukti Village MSME products using a press machine. The method used involves the application of press technology in the packaging process to ensure the compactness and durability of the product packaging. The press tool used is able to produce neater and more uniform packaging, thereby reducing the risk of product damage and improving packaging aesthetics. The results of applying the press show a significant increase in the quality of product packaging, both in terms of durability and visual appearance. This improvement in packaging quality has a positive impact on consumer experience, because they tend to choose products that are packaged well. Thus, the use of press equipment for packaging MSME products in Sukamukti Village has proven to be effective in improving product image and competitiveness in the market. This research provides recommendations for MSMEs in other villages to consider similar technology as part of their packaging strategy.